IMPLEMENTING TOTAL QUALITY MANAGEMENT TO ENHANCE ISLAMIC EDUCATION QUALITY: A CASE STUDY OF INTEGRATED ISLAMIC SCHOOLS IN JAMBI, INDONESIA - Rifai, Muhammad; Syukri, Ahmad; Fadillah, Fadillah (Antis Publisher, 2025)
Objective: This study aims to evaluate the implementation of Total Quality Management (TQM) in improving the quality of Islamic education at Integrated Islamic Schools (SIT) in Jambi Province. The background of this study rests on the need for integrated quality management in Islamic educational institutions, along with the increasing demands for the quality of professional and spiritual value-based educational services. Method: This research used a qualitative approach with a multicluster case study design on three SITs that were purposively selected. Data collection techniques included in-depth interviews, participatory observation, and documentation, while data analysis was conducted interactively through data reduction, presentation, and verification. Results: The results show that the main principles of TQM, such as total involvement, continuous improvement, and customer satisfaction orientation have begun to be internalized in school management. School principals play a central role in promoting a culture of quality, although there are still challenges in quality documentation, understanding internal customers, and limited human resource development. Novelty: An important finding of this study is the integration of TQM principles with Islamic values contextually applied in SIT management culture. This study provides theoretical contributions in the development of a spiritual-based TQM framework, as well as practical recommendations to strengthen quality assurance systems in Islamic educational institutions.